Reestructuración y diseño de nuevos perfiles para el área de ventas de repuestos en la compañía Divemotor - Flor Baldeon, Richard Vinder (2021)
The purpose of this document is to demonstrate an applied research study in the Divemotor company, this is done through a process improvement in the Central Region Spare Parts area, identifying the factors that affect non-compliance with the annual budget, productivity, reprocessing, teamwork, staff turnover and the work environment. As a general situation, it can be seen that the company is in a growth sector in Peru, in terms of unit sales, this in turn has had an impact on the sale of spare parts, encouraging the appearance of companies that have seen an excellent opportunity to do business with end customers, through only the sale of auto parts. At this juncture, it is extremely necessary for the area to review the spare parts sales process, specifically the assignment of customers in each of the sales channels, consequently the assignment of the customer to each seller, in addition to the team selection process of sales by the Human Resources. To start with the improvement study, the environment in which the company is located will be analyzed, as well as its organizational structure and internal processes, in this way it will be easier to detect through the indicators that are used to evaluate what is happening inside and outside the company, in order to find areas for improvement. Knowing this, the next step is to select the processes that have the greatest influence on these indicators, the same ones that will be sought to improve. Finding the opportunities for improvement makes it possible to propose the most convenient solution alternatives, which should include most, or all, of the options found. After that, a qualitative and quantitative analysis is carried out to identify the best proposal. When obtaining the solution to improve the processes, the engineering of this is presented to be able to start it with the support of the methods learned in the industrial engineering career. Then, each phase of the implementation process is detailed with its goals and objectives. Finally, the feasibility of the solution is verified through an economic and financial evaluation, taking into consideration the critical indicators of the spare parts sales business. xii With all this, the aim is to support the successful design and implementation of f the restructuring and redesign of the profiles that was carried out in the spare parts area in the automotive company, Divemotor. This improvement allowed the management of the area to be carried out more efficiently, through the application of industrial engineering tools.